EGR2 mutations define a new clinically aggressive subgroup of chronic lymphocytic leukemia - Young, Emma; Zenz, Thorsten; Damm, Friederike (Leukemia, 2017)
Recurrent mutations within EGR2 were recently reported in advanced-stage chronic lymphocytic leukemia (CLL) patients and associated with a worse outcome. To study their prognostic impact, 2403 CLL patients were examined for mutations in the EGR2 hotspot region including a screening (n=1283) and two validation cohorts (UK CLL4 trial patients, n=366; CLL Research Consortium (CRC) patients, n=490). Targeted deep-sequencing of 27 known/postulated CLL driver genes was also performed in 38 EGR2-mutated patients to assess concurrent mutations. EGR2 mutations were detected in 91/2403 (3.8%) investigated cases, and associated with younger age at diagnosis, advanced clinical stage, high CD38 expression and unmutated IGHV genes. EGR2-mutated patients frequently carried ATM lesions (42%), TP53 aberrations (18%) and NOTCH1/FBXW7 mutations (16%). EGR2 mutations independently predicted shorter time-to-first-treatment (TTFT) and overall survival (OS) in the screening cohort; they were confirmed associated with reduced TTFT and OS in the CRC cohort and independently predicted short OS from randomization in the UK CLL4 cohort. A particularly dismal outcome was observed among EGR2-mutated patients who also carried TP53 aberrations. In summary, EGR2 mutations were independently associated with an unfavorable prognosis, comparable to CLL patients carrying TP53 aberrations, suggesting that EGR2-mutated patients represent a new patient subgroup with very poor outcome.
Gesehen am 15.08.2018